Spiritualitas Dan Ketangguhan Mental Dalam Kisah Maryam Binti Imran: Telaah Psikologis Terhadap Narasi Al-Qur’an - Nasichah Nasichah; Faras Nasywa Ammara; Putri Karina Cahyadi (CV. ITTC INDONESIA, 2025)
This study aims to explore the mental resilience of Maryam binti Imran as narrated in the Qur'an, using an interdisciplinary approach that combines Islamic psychology and thematic Qur'anic interpretation. Maryam is portrayed as a spiritually strong and emotionally stable woman who was able to face severe psychological and social pressures—such as conceiving without a husband and bearing public stigma—with unwavering faith and dignity. This qualitative research is based on literature studies, using Qur'anic narratives and psychological theories as its primary sources. The findings reveal that spiritual practices such as dhikr, silence (fasting from speech), and surrender to the divine will serve as effective coping strategies in the face of adversity. Maryam’s resilience is also attributed to her upbringing in a pious environment under the care of Prophet Zakaria. These insights highlight the relevance of spirituality in developing psychological endurance, especially amid modern life challenges. This study contributes to the development of Islamic psychology and offers a Qur'anic-based model for spiritual coping and character education.